FIX&FOXY’s Distribution of Management - Krøgholt, Ida (Peripeti, 2023)
Krøgholt is unfolding FIX&FOXY’s way of working as distributed facilitation, where the participants facilitate each other, and thus through the theatre process develop an awareness of communication and observation.